Cost-Saving Early Diagnosis of Functional Pain in Nonmalignant Pain: A Noninferiority Study of Diagnostic Accuracy. (21st March 2016) - Cámara, Rafael J. A.; Merz, Christian; Wegmann, Barbara; Stauber, Stefanie; von Känel, Roland; Egloff, Niklaus
Abstract : Objectives . We compared two index screening tests for early diagnosis of functional pain: pressure pain measurement by electronic diagnostic equipment, which is accurate but too specialized for primary health care, versus peg testing, which is cost-saving and more easily manageable but of unknown sensitivity and specificity. Early distinction of functional (altered pain perception; nervous sensitization) from neuropathic or nociceptive pain improves pain management. Methods . Clinicians blinded for the index screening tests assessed the reference standard of this noninferiority diagnostic accuracy study, namely, comprehensive medical history taking with all previous findings and treatment outcomes. All consenting patients referred to a university hospital for nonmalignant musculoskeletal pain participated. The main analysis compared the receiver operating characteristic (ROC) curves of both index screening tests. Results . The area under the ROC curve for peg testing was not inferior to that of electronic equipment: it was at least 95% as large for finger measures (two-sidedp = 0.038 ) and at least equally as large for ear measures (two-sidedp = 0.003 ). Conclusions . Routine diagnostic testing by peg, which is accessible for general practitioners, is at least as accurate as specialized equipment. This may shorten time-to-treatment in general practices, thereby improving the prognosis and quality of life.